Asuransi Tanggung Jawab Produk dan Perlindungan Terhadap Konsumen - Ahmad Sudiro (Fakultas Hukum Universitas Islam Indonesia, 2014)
Product liability insurance is an important issue if it is associated with the protection of consumers. This is a form of producer’s responsibility in providing their protection to consumers who suffered losses as a result of using defective products. In this study, the problem is how the product liability insurance takes an important role in protecting the interests of consumers who suffered losses as a result of using a defective product, relating to the protection of consumers as the users of the product. This is a normative study employing the approach of legislation and conceptual. The results showed that the role of the insurance company as an insurer is taking over the responsibility of the manufacturer to the risk of losses due to product defects in the claims done by the consumers who suffered losses due to the defective product. Thus, the coverage of the product liability insurance is basically to protect and guarantee the right of consumers to the demands of compensation to producers.